Current and potential new treatment strategies for creatine deficiency syndromes - Gabriella Fernandes‐Pires; Olivier Braissant (2021)
Creatine deficiency syndromes (CDS) are inherited metabolic disorders caused by mutations in GATM, GAMT and SLC6A8 and mainly affect central nervous system (CNS). AGAT- and GAMT-deficient patients lack the functional brain endogenous creatine (Cr) synthesis pathway but express the Cr transporter SLC6A8 at blood-brain barrier (BBB), and can thus be treated by oral supplementation of high doses of Cr. For Cr transporter deficiency (SLC6A8 deficiency or CTD), current treatment strategies benefit one-third of patients. However, as their phenotype is not completely reversed, and for the other two-thirds of CTD patients, the development of novel more effective therapies is needed. This article aims to review the current knowledge on Cr metabolism and CDS clinical aspects, highlighting their current treatment possibilities and the most recent research perspectives on CDS potential therapeutics designed, in particular, to bring new options for the treatment of CTD.